2008
DOI: 10.1016/j.juro.2007.11.090
|View full text |Cite
|
Sign up to set email alerts
|

Nonrefluxing Neonatal Hydronephrosis and the Risk of Urinary Tract Infection

Abstract: Neonates with obstructive uropathy, severe hydronephrosis or hydroureteronephrosis have increased risk of urinary tract infection even without reflux, and antibiotic prophylaxis may be recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
68
2
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(77 citation statements)
references
References 19 publications
4
68
2
3
Order By: Relevance
“…As has been described in previous reports, [8] our study found that E. coli, pseudomonas aeruginosa, and klebsiella pneumoniae were the most common organisms cultured from urine. No patient with a urine culture positive for E. coli had a history of nephrostomy or pyeloplasty, unlike patients with urine cultures positive for other organisms.…”
Section: Discussionsupporting
confidence: 87%
“…As has been described in previous reports, [8] our study found that E. coli, pseudomonas aeruginosa, and klebsiella pneumoniae were the most common organisms cultured from urine. No patient with a urine culture positive for E. coli had a history of nephrostomy or pyeloplasty, unlike patients with urine cultures positive for other organisms.…”
Section: Discussionsupporting
confidence: 87%
“…The rationale for antibiotic prophylaxis in children with a history of prenatally detected uropathies includes prevention of UTIs, because infants with hydronephrosis are at increased risk (31,32). UTI rates seem to be as high as 40% in children with severe hydronephrosis (33). In a previous study, we estimated a cumulative incidence of UTIs as 39% and 11% at 36 months of age for severe and mild RPD, respectively (27).…”
Section: Discussionmentioning
confidence: 99%
“…Song et al [19] reported that 30% of 75 infants with grades III and IV hydronephrosis secondary to UPJO developed UTI when followed without antibiotic prophylaxis; the authors concluded that children with severe hydronephrosis should receive antibiotic prophylaxis. Lee et al [20] declared that antibiotic prophylaxis might be beneficial in obstructive hydronephrosis based on an observation that 39% of their patients with obstructive uropathy had UTI.…”
Section: Discussionmentioning
confidence: 99%